Satire and Moral Critique in Hadith-Based Digital Da’wah: Hijab Discourses on TikTok - Ahsani, Ahmad Amri; Zamzami, Mukhammad; Lutfi, Muhammad; Hegazy, Wael (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
This article problematizes the use of satirical narratives in TikTok-based digital da'wah that quote hadiths on the hijab, focusing on how satire functions both as moral critique and as a mechanism for producing stigma against Muslim women. This study examines how the TikTok account @musuhwanita constructs discourse through hadith-based satire and how these narratives shape social relations between men and women as well as configurations of religious authority in digital spaces. The central research question asks how discursive structures, social cognition, and ideological contexts operate in the satirical representation of the hijab. Empirically, the study is limited to an analysis of video content and audience comments published between August and September 2024, employing Teun A. van Dijk's Critical Discourse Analysis. This analysis is conducted from an Islamic normative perspective grounded in the principles of amr ma'ruf nahy munkar and da'wah digital ethics. This study contributes to digital Islamic studies by demonstrating how satirical da'wah reproduces and negotiates the meanings of hadith, hijab, and the representation of Muslim women within contemporary configurations of online religious authority.